Antecedents of Tourism Destination Reputation: The Mediating Role of Familiarity - Marinao-Artigas, E (Elsevier Ltd, 2015)
This study aims to test whether cognitive perception and affective evaluation of a tourism destination are significant antecedents of its reputation; and whether this relationship is mediated by familiarity. The proposed model was tested among 750 participants and results revealed that 40% of a destination s reputation is explained by familiarity. Familiarity in turn, is explained by cognitive perception (43%) and affective evaluation (14%). Findings confirmed the mediating role of familiarity in the relationship between cognitive perception, affective evaluation, and destination reputation. Given the important mediating role of familiarity, the various stakeholders in the tourism industry should strengthen familiarity in order to develop and enhance their reputation. © 2015 Elsevier Ltd.